2022
DOI: 10.1038/s41420-022-00839-3
|View full text |Cite|
|
Sign up to set email alerts
|

OTUB2 regulates KRT80 stability via deubiquitination and promotes tumour proliferation in gastric cancer

Abstract: OTUB2 is a deubiquitinating enzyme that contributes to tumor progression. However, the expression of OTUB2 and its prognostic importance in gastric cancer remain unclear. The expression of OTUB2 and KRT80 in GC tissues was investigated using western blotting, qRT-PCR, multiple immunofluorescence staining, and immunohistochemistry. For survival studies, Kaplan–Meier analysis with the log-rank test was used. The role of OTUB2 during GC proliferation was investigated using in vivo and in vitro assays. OTUB2 was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 32 publications
(29 reference statements)
1
19
0
Order By: Relevance
“…Our study supports the evidence that STC1 is a biomarker of breast cancer and promotes tumor growth and metastasis (Chang et al, 2015;Avalle et al, 2022). OTUB2 was reported to promote the progression of gastric cancer and colorectal cancer (Ouyang et al, 2022;Yu et al, 2022). As for breast cancer, a recent study reported that OTUB2 deubiquitinated and activated YAP/TAZ to promote cancer stemness and metastasis (Zhang et al, 2019), which confirms the reliability of our results.…”
Section: Discussionsupporting
confidence: 91%
“…Our study supports the evidence that STC1 is a biomarker of breast cancer and promotes tumor growth and metastasis (Chang et al, 2015;Avalle et al, 2022). OTUB2 was reported to promote the progression of gastric cancer and colorectal cancer (Ouyang et al, 2022;Yu et al, 2022). As for breast cancer, a recent study reported that OTUB2 deubiquitinated and activated YAP/TAZ to promote cancer stemness and metastasis (Zhang et al, 2019), which confirms the reliability of our results.…”
Section: Discussionsupporting
confidence: 91%
“…In their study, the proliferative capacities of AGS cells were significantly reduced by OTUB2 and KRT80 knockdown, respectively, using lentivirus technology compared with control cells, and both showed the same degree of effect. In addition, KRT80 supplementation restored growth and proliferation in OTUB2‐knockdown AGS cells, and KRT80 overexpression significantly promoted the cell growth capacity of MKN45 cells 24 . These results illustrate a relationship between KRT80 and GC cell proliferation, and a specific role for OTUB2 in GC cells is to regulate the expression of KRT80 proteins.…”
Section: Study Of Krt80 In Neoplastic Diseasesmentioning
confidence: 61%
“…As mentioned above, OTUB2 regulates KRT80 protein expression in a post‐transcriptional manner. Specifically, OTUB2 stabilizes the KRT80 protein via deubiquitylation of Lys48 and Lys63 linked, as a result KRT80 is not degraded by the proteasome mediated by ubiquitin 24 . This conclusion was supported by a ubiquitin pull‐down assay for flag‐tagged KRT80 and a Western blot assay.…”
Section: Study Of Krt80 In Neoplastic Diseasesmentioning
confidence: 81%
“…OTUB1 was found to be active in GC cell invasion and migration [ 89 ], but the underlying mechanism is unknown. Similar to OTUB1, OTUB2 was also found to be overexpressed in GC tissues and cell lines and predicted a poor prognosis [ 90 , 91 ]. Silencing OTUB2 inhibited GC cell growth, metastasis, and sphere formation.…”
Section: Otus and Gcmentioning
confidence: 99%
“…Silencing OTUB2 inhibited GC cell growth, metastasis, and sphere formation. Mechanistically, OTUB2 acts as a potential driver oncogene in GC by deubiquitinating and stabilizing the demethylase KDM1A, and epithelial keratin KRT80 [ 90 , 91 ]. As previously reported, KDM1A and KRT80 contributed to GC progression by regulating KLF2 expression and the PI3K/Akt pathway, respectively [ 172 , 173 ].…”
Section: Otus and Gcmentioning
confidence: 99%